Visions of the future : chemistry and life science - Thompson, J. M. T. (Cambridge University Press, 2001)
Writing in a popular and well illustrated style, leading young scientists describe their research and give their visions of future developments in Chemistry and Life Science. The book conveys their excitement and enthusiasm and offers definitive reviews for anyone with a general interest in science.
Keywords: Chemistry.; Life sciences.; Chemistry; Biological Science Disciplines; Chimie.; Sciences de la vie.; chemistry.; biological sciences.; SCIENCE -- Chemistry -- General.; Life sciences